Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Kinerja Pegawai Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia (BKPSDM) Kabupaten Lebak - Vally Adha Dwianto; Irawan; Suhroji Adha (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
The aim of this research is to determine the influence of work discipline and work motivation on the performance of employees of the Lebak Regency Personnel and Human Resources Development Agency (BKPSDM). The data analysis technique used in this research is quantitative. In this research, data collection was carried out by distributing questionnaires. This research has a sample and population of 37 respondents. The data obtained was analyzed using validity tests, reliability tests, multiple linear regression analysis, classical assumption tests, hypothesis tests using SPSS version 29. The results of the analysis prove that partially, work discipline and work motivation each have a significant effect on employee performance. Likewise, work discipline and work motivation simultaneously have a significant effect on employee performance.